120k views
5 votes
Consider the binomial (u^2 − v^3)^6.

a. Find the term that contains v^6.
b. Find the term that contains u^6.
c. Find the fifth term.

User Abraham P
by
6.0k points

1 Answer

3 votes

Answer:

The answer to your question is:

Explanation:

(u² - v³)⁶ = u¹² - 6(u²)⁵(v³) + 15(u²)⁴(v³)² - 20(u²)³(v³)³ + 15(u²)²(v³)⁴ - 6(u²)(v³)⁵ +

(v³)⁶

= u¹² - 6u¹⁰v³ + 15u⁸v⁶ - 20u⁶v⁹ + 15u⁴v¹² - 6u²v¹⁵ + v¹⁸

a.- Find the term that contains v⁶ = 15u⁸v⁶

b.- Find the term that contains u⁶ = - 20u⁶v⁹

c.- Find the fifth term = 15u⁴v¹²

User Gabagool
by
5.6k points